1991
DOI: 10.2307/1542438
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characterization of Ion Transporting and Respiratory Filaments in the Gills of Procambarus clarkii

Abstract: Individual gill filaments of the freshwater crayfish Procambarus clarkii were determined to be either predominantly respiratory or transporting. Silver staining revealed that the filaments within the central bed of the gills formed silver deposits whereas filaments at the margins and the entire sixth pleurobranch formed no deposits. Designation of the silver staining gills as predominantly transporting and unstained filaments as predominantly respiratory was substantiated by ultrastructural analyses and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 49 publications
2
33
0
4
Order By: Relevance
“…This is notable as brachyuran gills are typically either respiratory or osmoregulatory in nature, with AgNO 3 staining typically confined to just the osmoregulating gills. For example, only the posterior gills undergo staining in C. sapidus and many other brachyurans (Copeland and Fitzjarrell, 1968), and while some lamellae in all gills show staining in FW crayfish, it is localized to the central filaments of each gill (Dickson et al, 1991;Khodabandeh et al, 2005). AgNO 3 staining of larval H. rubra revealed that ion-transporting gills develop at late zoeal stages (i.e.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…This is notable as brachyuran gills are typically either respiratory or osmoregulatory in nature, with AgNO 3 staining typically confined to just the osmoregulating gills. For example, only the posterior gills undergo staining in C. sapidus and many other brachyurans (Copeland and Fitzjarrell, 1968), and while some lamellae in all gills show staining in FW crayfish, it is localized to the central filaments of each gill (Dickson et al, 1991;Khodabandeh et al, 2005). AgNO 3 staining of larval H. rubra revealed that ion-transporting gills develop at late zoeal stages (i.e.…”
Section: Research Articlementioning
confidence: 99%
“…However, all gills in crayfishes and shrimps possess MRCs and are involved in osmoregulation, although some areas of individual gills remain specialized for respiration (Wheatly and Henry, 1987;Dickson et al, 1991;McNamara and Lima, 1997;Ordiano et al, 2005;Huong et al, 2010). Active salt absorption in the MRCs is accomplished via a suite of ion transporters and supporting enzymes (Evans et al, 2005;Henry et al, 2012): in this context, Na + absorption occurs via a combination of apical Na + /H + exchange, Na + /K + /2Cl -co-transport, Na + channels and the basolateral Na + /K + -ATPase (NKA), while Cl -absorption is accomplished via apical co-transport, Cl -/HCO 3 -exchange and basolateral Cl -channels (reviewed in Freire et al, 2008;Charmantier et al, 2009;Henry et al, 2012;McNamara and Faria, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Silver staining has been used to identify putative osmoregulatory epithelia in a number of insects (Krogh, 1939) and crustaceans (Koch, 1934;Ewer and Hatlingh, 1952;Talbot et al, 1972;Barra et al, 1983;Felder et al, 1986;Dickson and Dillaman, 1991;Kikuchi and Matsumasa, 1993;Lindhjem et al, 2000;Haond et al, 2001). The appearance of the silverstaining patch on the surface of the embryo at gastrulation coincided with the acquisition of hyper-osmoregulatory capacity, tempting the suggestion that the patch is concerned with ion transport.…”
Section: Sites Of Uptake and Excretion Of Water And Salts In Embryosmentioning
confidence: 99%
“…Many studies have shown that gills are the primary organs for salt transport in crabs 8,9,10 and lobsters 11 . They utilize apical membrane branchial Na /HCO 3 -exchange powered by a basal membrane Na + / K + -ATPase.…”
Section: Introductionmentioning
confidence: 99%